SN 2020pvb: A Type IIn-P supernova with a precursor outburst - Elias-Rosa, N.; Brennan, S.J.; Benetti, S.; Cappellaro, E.; Pastorello, A.; Kozyreva, A.; Lundqvist, P.; Fraser, M.; Anderson, J.P.; Cai, Y.Z.; Chen, T.W.; Dennefeld, M.; et al. (EDP Sciences, 2025)
We present photometric and spectroscopic datasets for SN 2020pvb, a Type IIn-P supernova (SN) that is similar to SNe 1994W, 2005cl, 2009kn, and 2011ht, with a precursor outburst detected (PS1 w band ∼- 13.8 mag) around four months before the B-band maximum light. SN 2020pvb presents a relatively bright light curve that peaked at MB = -17.95 ± 0.30 mag and a plateau that lasted at least 40 days before going into solar conjunction. After this, the object was no longer visible at phases > 150 days above - 12.5 mag in the B band, suggesting that the SN 2020pvb ejecta interact with a dense, spatially confined circumstellar envelope. SN 2020pvb shows strong Balmer lines and a forest of Fe II lines with narrow P Cygni profiles in its spectra. Using archival images from the Hubble Space Telescope, we constrained the progenitor of SN 2020pvb to have a luminosity of log(L/L⊙)≤5.4, ruling out any single star progenitor over 50 M⊙. SN 2020pvb is a Type IIn-P whose progenitor star had an outburst*sim;0.5 yr before the final explosion; the material lost during this outburst probably plays a role in shaping the physical properties of the SN.